Effects of chlorination and combined UV/Cl2 treatment on endotoxin activity and inhalation toxicity of lipopolysaccharide, gram-negative bacteria and reclaimed water. (15th May 2019) - Xue, Jinling; Zhang, Jinshan; Qiao, Juan; Lu, Yun
Abstract: Disinfection processes were applied in reclaimed water plant to eliminate pathogens and control the related health risk during water reuse. However, extra problems might emerge such as the released free endotoxins from the ruptured cell wall of gram-negative bacteria. Endotoxins can induce lung inflammatory responses after inhalation, which has been neglected in the water quality regulation, and the removal of endotoxin was not under consideration in the process of reclamation. In the present study, two well-known disinfection processes, chlorination and combined UV/chlorine (UV/Cl2 ), were performed to test the removal efficiency of endotoxin activity, as well as the inflammation inducing ability. In the pure LPS solution, UV/Cl2 treatment significantly reduced both endotoxin activity and lung inflammation responses with better oxidizability of the generated hydroxyl radical. However, its performance on bacteria liquid and real secondary effluent was more complicated. The cell wall-bound LPS have lower endotoxin activities and inflammation inducing ability. Immediately after the cell wall was destroyed, the bound LPS were released to the solution to be free LPS, which dramatically increased both the endotoxin activity and inflammation inducing ability of the water. When these free endotoxins were continuously oxidized, the endotoxin activity and inflammatory response decreased again but not to the background level. Therefore, the inflammation inducing ability of reclaimed water could not be removed efficiently. These results suggest that in spite of its high oxidability, UV/Cl2 treatment is not capable of removing the endotoxin-based toxicity, and other technologies are necessary to control endotoxin levels in reclaimed water. Graphical abstract: Image 1 Highlights: UV/Cl2 reduced more inflammation inducing ability of endotoxin than chlorination. The aggregate size of free endotoxin reduced significantly after UV/Cl2 treatment. Unlike chlorination, UV/Cl2 reduces endotoxin activity and toxicity simultaneously. Insufficient oxidation might increase the toxicity of reclaimed water. Oxidation-released free endotoxin can be regard as a new disinfection byproduct.